Pengaruh Pertumbuhan Penjualan, Profitabilitas, Struktur Modal, dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Asofyan, Arif Andi; Indrati, Menik (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to examine the effect of sales growth, profitability, capital structure, and corporate social responsibility (CSR) on firm value in companies listed in the LQ45 index during the 2022–2024 period. This research also intends to provide insights for investors in evaluating the factors that influence firm value as a basis for investment decision-making, including sales growth, profitability, capital structure, CSR, and firm value. The population of this study consists of 45 LQ45 companies, with a sample of 32 companies selected using purposive sampling based on specific criteria, resulting in 96 total observations. The research results show that sales growth and CSR do not affect firm value. Meanwhile, profitability and capital structure hurt firm value. This study concludes that sales growth has not yet become a strong fundamental signal for investors, as it does not always reflect sustainable performance. High profitability, in fact, has a negative effect on firm value, which may be due to a mismatch between short-term profits and the long-term prospects expected by investors. A high capital structure signals greater financial risk, thereby reducing investor confidence in the company. Meanwhile, CSR has not had a significant impact on firm value, possibly due to low disclosure quality or a lack of investor attention to sustainability issues.